Strategi Guru PAK dalam Menanamkan Nilai Kasih dan Pengampunan melalui Metode Inkuiri pada Siswa Kelas IX SMP Rehobot Boarding School Palangka Raya - Rohit Rohit; Wandi Wandi (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to examine the strategies employed by Christian Religious Education teachers to instill the values of love and forgiveness through the inquiry method among ninth-grade students at Rehobot Boarding School Palangka Raya. The research also analyzes the supporting factors and challenges encountered during its implementation. The study was motivated by the persistence of peer conflicts, difficulties in practicing forgiveness, limited student engagement, and low participation in Christian Religious Education classes. A qualitative descriptive approach was employed using purposive sampling. The primary informant was the Christian Religious Education teacher, while additional informants included ninth-grade students, the school principal, and dormitory supervisors. Data were collected through observation, interviews, and document analysis and were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the inquiry method, implemented through observing, questioning, discussing, problem analysis, and reflection on biblical teachings, encourages active student participation and strengthens the internalization of love and forgiveness in daily life. The effectiveness of this strategy is supported by teacher competence, a conducive learning environment, adequate educational facilities, and collaboration between the school and parents. However, its implementation is constrained by differences in students’ abilities, limited instructional time, low learning motivation among some students, and the influence of technology and social media. The study concludes that the inquiry method is an effective strategy for fostering Christian character by cultivating the values of love and forgiveness.